The Prime Mover and the Problem of Universal Unanimity - Litvinas, Vytautas Rimvydas (Problemos, 1999)
The realization of Platonic stratified universality image arises difficulties to set a unifying foundation. Scrutinizing the meaning of the phenomenon and idea Aristotle solves their interrelation by introducing notions of potential and actual existence and relating those two existential modes in the highest actuality of Primary mover. Material and form are the specific aspects of Primary mover’s activity, Universal components unified in actual infinity (this way the Primary mover can be called). That is Aristotle considers the unanimous Universal as an epiphany of Absolute filling up all the ontic existence levels.